Response of underwater photosynthesis to light, CO2, temperature, and submergence time of Taxodium distichum, a flood-tolerant tree - Guo, Jinbo; Xue, Jianhui; Yin, Yunlong; Pedersen, Ole; Hua, Jianfeng (Frontiers in Plant Science, 2024)
Partial or complete submergence of trees can occur in natural wetlands during times of high waters, but the submergence events have increased in severity and frequency over the past decades.Taxodium distichum is well-known for its waterlogging tolerance, but there are also numerous observations of this species becoming partially or complete submerged for longer periods of time.Consequently, the aims of the present study were to characterize underwater net photosynthesis (PN) and leaf anatomy of T. distichum with time of submergence.We completely submerged 6 months old seedling of T. distichum and diagnosed underwater (PN), hydrophobicity, gas film thickness, Chlorophyll concentration and needles anatomy at discrete time points during a 30-day submergence event. We also constructed response curves of underwater PN to CO2, light and temperature.During the 30-day submergence period, no growth or formation new leaves were observed, and therefore T. distichum shows a quiescence response to submergence. The hydrophobicity of the needles declined during the submergence event resulting in complete loss of gas films. However, the Chlorophyll concentration of the needles also declined significantly, and it was there not possible to identify the main cause of the corresponding significant decline in underwater PN. Nevertheless, even after 30 days of complete submergence, the needles still retained some capacity for underwater photosynthesis under optimal light and CO2 conditions. However, to fully understand the stunning submergence tolerance of T. distichum, we propose that future research concentrate on unravelling the finer details in needle anatomy and biochemistry as these changes occur during submergence.